(untitled) (Research, Society and Development, 2020)
This study aims to uncover the emergence of inclusion in pedagogical mediation in the teaching and learning of basic education in Brazilian indigenous school education in current times of public technology politics. The indigenous school discussed in this research brings the Digital Information and Communication Technologies (TDIC) as a centrality to expand the construction of knowledge in the teaching process and the learning of indigenous students throughout the formation process. It proposes in the study to point out the potentialities of the use of digital methodologies to teach and learn in indigenous schools, preserving their traditional knowledge, science and culture in association with a specific and differentiated teaching, intercultural, bilingual and within their own learning processes. The study was engendered within the quali-quantitative approach; About the objectives it is anchored in exploratory research; About the procedures it fits in the bibliographic research in association with documentary research in all phases of the study.The results indicated that the effectiveness of technological policies in indigenous school education at the present historical educational moment has potential for improvement in teaching and learning. It is verified that the implementation of public policies on technologies in Brazilian indigenous school education will corroborate the eradication of digital exclusion and technological illiteracy and train indigenous students subject to legal rights with skills and digital abilities. However, the emergence of the Ministry of Education consolidates and first implements basic infrastructure and electricity for this type of education in the country to then promote broad coverage of implementation of public policy in TDIC, aiming to opportunize all students to access education through digital tools.